Visual Artistic Images in the Quran: An Analysis of Selected Verses from Surah Al Baqarah - Abed, Farhan Obed (2015)
Muslim scholars have undertaken various methods to interpret the Quran in order to ease Muslims and man in general to understand and study its contents. However, the scholars have only discussed undetailed artistic perspective from the Quran. They do not rely on the application of functional elements of art on the verses that contain depictions, but instead present a formal analysis of the verses. Knowledge in the arts field is a requirement in the comprehension and application of the art elements against the Quranic verses in order for an in depth understanding from the arts perspective. Due to a small and limited number of work from scholars of Islamic stream or linguistic studies, Islamic references from the arts perspective in understanding the Quran is very inadequate. In response, this qualitative research attempts to fill in the gap by undertaking an artistic study on the aesthetic side of the verses containing artistic images in SUrah Al-Baqarah from the most prominent interpretation books and then comparing them to the opinions of Muslim scholars and well-known Muslim artists. Then, in order to explore the Quran artistically, three main pillars of art were applied against these verses to make it much comprehensible. Muslim artists have had a limited scope in approaching the Quran while the Quran speaks of many unseen things and these verses used imagery approaches to describe the unseen abstract objects that can only be felt and imagined.